Transcriptomics and magnetic resonance imaging in major psychiatric disorders - Fan, Jing-Wen; Gu, Yue-Wen; Wang, Dong-Bao; Liu, Xiao-Fan; Zhao, Shu-Wan; Li, Xiao; Li, Baojuan; Yin, Hong; Wu, Wen-Jun; Cui, Long-Biao (Frontiers in Psychiatry, 2023)
Major psychiatric disorders create a significant public health burden, and mental disorders such as major depressive disorder, bipolar disorder, and schizophrenia are major contributors to the national disease burden. The search for biomarkers has been a leading endeavor in the field of biological psychiatry in recent decades. And the application of cross-scale and multi-omics approaches combining genes and imaging in major psychiatric studies has facilitated the elucidation of gene-related pathogenesis and the exploration of potential biomarkers. In this article, we summarize the results of using combined transcriptomics and magnetic resonance imaging to understand structural and functional brain changes associated with major psychiatric disorders in the last decade, demonstrating the neurobiological mechanisms of genetically related structural and functional brain alterations in multiple directions, and providing new avenues for the development of quantifiable objective biomarkers, as well as clinical diagnostic and prognostic indicators.